Anthropotechniques and Homo Ludens Dimension in Higher Education in Colombia 1935-1992 - Peñuela Contreras, Diana Milena (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this article, training exercises functioning within the shaping of the homo ludens dimension are explored. These exercises are characteristic of specific dynamics that can be grouped as complementary education in the 20th century University – social extension and student welfare -. To do so, emphasis will be placed on the anthropotechnics notion methodological applications in order to illustrate how active training exercises involved production techniques of themselves – psychoanthropotechniques – and of others – social anthropotechniques – in the shaping of a pragmatic ethics at the university level. The article is divided into four segments: Anthropotechniques and homo ludens dimension, Complementary training in higher education, active and modulating adaptation, Anthropotechnique exercises and shaping of the homo ludens formative dimension at the university, and Pragmatic ethics and homo ludens.